Knowledge of Parents about Thalassemia in Tabuk City: A Cross-Sectional Study - Alblewi, Sawsan Mohammed; Alatawi, Amirah M; Hanafy, Ehab Mahmoud; Althobaiti, Faisal Mayudh; Al-Balawi, Abdulelah Hamad; Alamrani, Faisal Mohammed; Ajwah, Yazeed Mahmoud; Albalawi, Omar Muslih; Alquayr, Mohammed Majed; Alhamdi, Sultan Ibrahim (Makara Journal of Health Research, 2026)
Background: Thalassemia is a common inherited blood disorder and remains a significant public health concern in Saudi Arabia. Parental knowledge is essential for effective prevention, screening, and early intervention. This study aimed to assess the knowledge of thalassemia among parents in Tabuk City, Saudi Arabia, and identify factors associated with knowledge levels. Methods: A cross-sectional study was conducted among 392 parents residing in Tabuk City between March and May 2025. Data were collected using a validated Arabic questionnaire distributed online. Knowledge was assessed using 21 items covering general thalassemia knowledge, thalassemia major, carrier status, and prevention. Knowledge levels were categorized according to Bloom’s cut-offs. Associations were examined using chi-square tests and multivariable logistic regression. Results: The median knowledge score was 7 (IQR 1–12; possible range 0–21). Overall, 68.1% of participants demonstrated poor knowledge, 29.1% moderate knowledge, and 2.8% good knowledge. Important misconceptions were identified regarding inheritance, carrier status, diagnostic testing, and prevention. Male sex was independently associated with poor knowledge (AOR = 2.34, 95% CI: 1.38–3.96, p = 0.002). Conclusion: Parental knowledge regarding thalassemia in Tabuk City was generally inadequate. Targeted educational interventions, genetic counseling, and screening programs are needed to improve awareness and support disease prevention.